2017
DOI: 10.18203/2349-2902.isj20173877
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of management of grade III hemorrhoids by Harmonic Scalpel technique versus conventional surgical technique (Milligan Morgan method)

Abstract: Background: The study aimed to compare the management of Grade III hemorrhoids by conventional Milligan Morgan versus Harmonic scalpel hemorrhoidectomy with respect to the intraoperative time, intra operative blood loss, length of hospital stays, postoperative outcome based on immediate and late complications and activity resumption, recurrence and cost.Methods: In this prospective study, a total of 60 patients, 30 patients undergoing Harmonic Scalpel hemorrhoidectomy and 30 patients undergoing Milligan Morgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
2
0
0
Order By: Relevance
“…In our study anal abscess and anal stenosis were recorded as a complication in MM but they weren't recorded in HS. Anal incontinence was not recorded in either group this was similar to Lim study in 2016 who also state that no anal incontinence was reported in his study (12).…”
Section: Results:-supporting
confidence: 89%
“…In our study anal abscess and anal stenosis were recorded as a complication in MM but they weren't recorded in HS. Anal incontinence was not recorded in either group this was similar to Lim study in 2016 who also state that no anal incontinence was reported in his study (12).…”
Section: Results:-supporting
confidence: 89%
“…In this study patients satisfaction is excellent with harmonic scalpel group A than Milligan Morgan group B and this is consistent with comparative study done on 60 patients by A. Thiyagarajan compared Harmonic Scalpel haemorrhoidectomy versus Milligan Morgan haemorridectomy, he concluded that harmonic Scalpel had the lowest pain score and the highest satisfaction score (Thiyagarajan & Bhatnagar, 2017).…”
Section: Discussionsupporting
confidence: 89%